Reformulation and optimization of birth certificate services of the population and civil registration office serang district - Permana, Deni; Saepudin, Eli Apud; Kamilah, Fithrotul (Institute Of computer Science (IOCS), 2025)
The rate of delay in issuing birth certificates in Indonesia is significant, potentially hampering children's access to basic rights such as education, health and other public services. Based on data compiled by the Central Statistics Agency (BPS) and other relevant institutions, it is estimated that more than 20% of births in some regions in Indonesia are not recorded on time. This delay is caused by various factors, including limited access to civil registration services, lack of awareness about the importance of birth certificates, and technical and bureaucratic obstacles that hinder the registration process. As a result, many children do not have birth certificates within the appropriate timeframe. This study aims to improve the quality of birth certificate services at the Disdukcapil of Serang Regency to make it faster, easier and more affordable for the community. Through a series of analysis and evaluation, several innovative solutions were found that can be implemented. With this reformulation, it is expected that the community can obtain their children's birth certificates more quickly, so that children can access various public services such as education and health without obstacles. The type of research used in this study is descriptive research with a qualitative approach. The location of this research was Serang Regency. This research aims to reformulate and optimize the implementation of this program.